Luluk Discourse in Patanda Kadupipi Ceremony of the Kambera Society - Restisary Nduka; NFN Suhandano (Balai Bahasa Kalimantan Tengah, 2023)
Luluk discourse is one of the linguistic elements used to communicate in traditional wedding ceremonies by the Kambera society. This study aims to analyze the structure of luluk discourse and explain its linguistic characteristics. This research uses the ethnographic study of communication with a qualitative descriptive method. The results revealed that the structure of luluk discourse in the patanda kadupipi stage was arranged in two dialog sessions, in the first session discussing the yelling to kandihang, discussion of customary fines, discussion of dates, discussion of offerings, and in the end closing the first session. Furthermore, the second session comprises the yelling to kandihang, date agreement, negotiation of offerings, and agreement on the amount of offerings. Luluk discourse has literary discourse characteristics consisting of language style, ritual language, and rhythmic language. AbstrakWacana luluk merupakan salah satu unsur kebahasanan yang digunakan untuk berkomunikasi dalam upacara pernikahan adat oleh masyarakat Kambera. Tujuan dari penelitian ini adalah menganalisis struktur wacana luluk dan menjelaskan karakteristik kebahasaannya. Penelitian ini menggunakan kajian etnografi komunikasi dengan metode deskriptif kualitatif. Hasil penelitian mengungkapkan bahwa struktur wacana luluk dalam tahapan patanda kadupipi tersusun dua sesi dialog. Sesi pertama membahas penyahutan kandihang, denda adat, tanggal, seserahan, penutupan sesi pertama. Selanjutnya pada sesi kedua tersusun atas penyahutan kandihang, kesepakatan tanggal, negosiasi seserahan, dan jumlah seserahan. Wacana luluk memiliki karakteristik wacana literer yang terdiri dari gaya bahasa, bahasa ritual, dan bahasa berirama.